Pembuatan Website Penerimaan Peserta Didik Baru (PPDB) Man 3 Sragen - Vera Wati; Moh Erkamim (Universitas Pahlawan Tuanku Tambusai, 2022)
A website is domain page that contains information that aims to enable people to inter-connect. Through the website, it is also one of the media to improve the image of both institutions and agency, related to web pages that are capable of displaying multimedia documents such as text, images, videos, and even animations that are made as attractive. In the case of MAN 3 Sragen school which uses the New Student Admissions website (PPDB), used to inform the public which aims to help schools manage the implementation of PPDB selection and provide convenience to the community, especially parents or guardians of prospective students in obtaining information. School-related information can be easily accessed anywhere and anytime because it is online. In addition, during the Covid-19 pandemic, the role of schools is to participate in trying to minimize community mobility. So based on the results of the evaluation of the implementation of community service with assistance and maintenance of the PPDB website, it is easy to understand by the manager and the school takes steps to inform and disseminate to the public.